Thermal performance of computer micro-processor using microchannel heat sink with nanofluids - Tan Hin Joo, Tony (2016)
In the rapid development of electronic technology, the demand of high capacity in computer performance is increasing every year. The higher the performance of computer the higher the heat will be released from the computer processor. Without proper management of the heat release, the generated high heat will cause computer performance deteriorate due to high temperature and may cause damage consequently. Furthermore, the continuous miniaturization process of electronic component has contributed impact to the size of cooling system which is incorporated with the electronic component. As commonly found in the current technology of cooling system, the conventional size of cooling system is used, and various medium are applied through the cooling system for heat removal purpose. The heat removal capacity of conventional cooling system is limited which is not able to dispel the high heat that generated from high performance computer processor. Furthermore, the larger size of the conventional cooling system can not be fitted into the smaller size of electronic components of the processor. As a result, a proper approach of managing the high heat issue and proper physical size of cooling system is required, in which microchannel heat sink is introduced. In the research work, various operating conditions (pressure drop [range: 20Pa – 38Pa], temperature [range: 342K – 354K] and Reynolds Number [range: 70 – 1150]), physical dimensions and channel configurations (rectangular, triangular and trapezoidal) are considered and analysed in order to investigate their impact on the microchannel heat sink performance in terms of pressure drop, pumping power, thermal resistance, and heat transfer coefficient. Besides this, various cooling working medium has been used such as distilled water and nanofluid (Distilled Water H2O + Alumina Al2O3 and Distilled Water H2O + Silica SiO2) with various concentrations of nanoparticles (1%, 2% and 3% concentration). Simulation work by applying Finite Volume Method (FVM) in FLUENT software has been carried out to simulate the engineering results for the performance of microchannel heat sink. It is found that the physical dimension and geometrical channel configuration have obvious impact on the microchannel heat sink performance in which the case of rectangular channel that provides the highest heat transfer performance. Besides this, the research work also shows that the effect of different types and concentrations (1%, 2% and 3% concentrations) of nanoparticles within cooling medium plays important role onto the microchannel heat sink performance. The increment of cooling performance by 40% can be achieved by adding nanoparticles into cooling medium as compared with pure distilled water. Furthermore, the increment of cooling rate also can be achieved by the increment of nanoparticles concentration. In the research work, nanofluid Alumina provides the higher cooling rate as compare with pure distilled water and nanofluid Silica due to the effect of high thermal conductivity. However, the small amount of nanoparticles concentration would not affect hydrodynamic performance of microchannel heat sink. As a result, the physical dimension, channel geometrical configurations, existence of nanoparticles within cooling medium are vital factors that able to affect and incur obvious impact on the performances of microchannel heat sink hydrodynamically and thermally. To ensure the result of the simulation work above is reliable, the experimental works have been carried out for validation and comparison.